2016
DOI: 10.3389/fnhum.2016.00627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Adult Attachment Projective Picture System on Oxytocin and Cortisol Blood Levels in Mothers

Abstract: Oxytocin, a small neuropeptide of nine amino acids, has been characterized as the “hormone of affiliation” and is stimulated, for instance, in mothers when interacting with their offspring. Variations in maternal oxytocin levels were reported to predict differences in the quality of care provided by mothers. In this study, the Adult Attachment Projective Picture System (AAP) as a valid measure to assess attachment representations was used as an activating attachment-related stimulus. We investigated whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 58 publications
1
30
1
Order By: Relevance
“…However, this association should be interpreted with caution due to the relatively small sample size. In contrast to studies showing an effect of the attachment representation on the OXT/ OXTR system, previous studies from our group revealed opposite results with no attachment-depending effects of baseline or plasma OXT levels in mothers measured immediately after the AAP (Krause et al, 2016 ). Therefore, studies investigating the OXT/ OXTR system in securely and insecurely attached individuals found inconsistent results, especially if peripheral plasma OXT levels were determined.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, this association should be interpreted with caution due to the relatively small sample size. In contrast to studies showing an effect of the attachment representation on the OXT/ OXTR system, previous studies from our group revealed opposite results with no attachment-depending effects of baseline or plasma OXT levels in mothers measured immediately after the AAP (Krause et al, 2016 ). Therefore, studies investigating the OXT/ OXTR system in securely and insecurely attached individuals found inconsistent results, especially if peripheral plasma OXT levels were determined.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies observed that maltreated individuals showed a higher OXT release in response to a psychological stressor (Seltzer et al, 2014 ). In contrast, our own studies also showed no CM-affected plasma OXT alterations, but a significant increase in peripheral OXT levels in response to an attachment stressor (AAP) (Krause et al, 2016 ). Therefore, the OXT plasma level of maltreated participants might overreact in response to an acute stressor, while it is unchanged with respect to OXT levels in a resting condition.…”
Section: Discussionmentioning
confidence: 80%
“…Combined, our results do not support the hypothesis that the social experience of choir singing promotes the secretion of OXT from the neurohypophysis into circulation and eventually in saliva. This hypothesis was based on two lines of reasoning: (i) an earlier study reporting an increase in salivary OXT concentrations (139% of basal) after 30 min of choir rehearsal, including 10 min of warm-up exercises and repeatedly singing the pop-song “California Dreaming” (Kreutz, 2014 ); and (ii) reports of other positive social experiences resulting in OXT secretion, such as intense parent-child interactions, massage, gossiping with friends, and loving interactions between participants and their dogs (Grewen et al, 2005 ; Gonzaga et al, 2006 ; Feldman et al, 2010 ; Beetz et al, 2013 ; Kim et al, 2014 ; Tsuji et al, 2015 ; Krause et al, 2016 ; Lebowitz et al, 2016 ; Brondino et al, 2017 ). Of course, it may be that positive bilateral interactions or the powerful intimate bond between parents and their children, romantic partners, or dogs and their owners are needed to trigger the OXT system to a quantifiable extent—aspects that are missing from choir singing.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, peripheral OXT secretion has been reported in response to intense social experiences including parent-child interactions, recalling a romantic event, warm contact with a loved one, and gossiping with close friends (Grewen et al, 2005 ; Gonzaga et al, 2006 ; Feldman et al, 2010 ; Kim et al, 2014 ; Krause et al, 2016 ; Lebowitz et al, 2016 ; Brondino et al, 2017 ). However, OXT is also secreted in response to various kinds of stress (Pierrehumbert et al, 2010 ; de Jong et al, 2015 ; Brown et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consisting of nine amino acids, this neuropeptide is produced by PVN and SON. Through axonal transport OT is centrally released to hippocampus, amygdala, striatum, hypothalamus, nucleus accumbens, and the central brain in response to social interactions and stressors (27)(28)(29)(30). In line with the Calm and Connect Model (31), which assumes that bonding, experienced through touch and social affection, leads to OT production and thus positively reinforces social connection, several studies have linked insecure attachment patterns to impairments of the OTsystem (23,27,29,32).…”
Section: Introductionmentioning
confidence: 99%